Oral vaccination with recombinant Lactobacillus plantarum encoding Trichinella spiralis inorganic pyrophosphatase elicited a protective immunity in BALB/c mice. - Chen Xi Hu (Public Library of Science (PLoS), 2021)
Background Trichinellosis is a serious zoonotic disease distributed around the world. It is needed to develop a safe, effective and feasible anti-Trichinella vaccine for prevention and control of trichinellosis. The aim of this study was to construct a recombinant Lactobacillus plantarum encoding Trichinella spiralis inorganic pyrophosphatase (TsPPase) and investigate its immune protective effects against T. spiralis infection. Methodology/principal findings The growth of recombinant L. plantarum was not affected by TsPPase/pSIP409-pgsA' plasmid, and the recombinant plasmid was inherited stably in bacteria. Western blot and immunofluorescence assay (IFA) indicated that the rTsPPase was expressed on the surface of recombinant L. plantarum. Oral vaccination with rTsPPase induced higher levels of specific serum IgG, IgG1, IgG2a and mucosal secretory IgA (sIgA) in BALB/c mice. ELISA analysis revealed that the levels of IFN-γ and IL-4 released from spleen, mesenteric lymph nodes and Peyer's patches were evidently increased at 2-4 weeks following vaccination, compared to MRS (De Man, Rogosa, Sharpe) medium control group (P < 0.05). Immunization of mice with rTsPPase exhibited a 67.18, 54.78 and 51.91% reduction of intestinal infective larvae, adult worms and muscle larvae at 24 hours post infection (hpi), 6 days post infection (dpi) and 35 dpi, respectively (P < 0.05), and the larval molting and development was significantly inhibited by 45.45% at 24 hpi, compared to the MRS group. Conclusions TsPPase plays a crucial role in T. spiralis molting and development, oral vaccination with rTsPPase induced a significant local mucosal sIgA response and systemic Th1/Th2 immune response, and immune protection against T. spiralis infection in BALB/c mice.